Factores potenciadores de valores cívicos, patrióticos e interculturales en la enseñanza básica - Reascos Landin, Pamela Estefanía (Machala, 2020)
In order to determine which factors contribute to the empowerment of what is ours by children in the context of Social Sciences in Basic Education, a bibliographic review study was carried out, systematized through content analysis methods. . Among the main findings, it was determined that among these factors the literature points to interactive methodologies, the effectiveness of intercultural education, curricular relevance and teacher training. In this empowerment, interactive methodologies aimed at teaching and learning from an integrative and interdisciplinary vision, of active participation, cooperation and collaboration in the collective construction of knowledge, transversalized by intercultural knowledge and civic, patriotic and ethical values00000000000000000000000000000000000000000000000000000000 promote cognitive development, procedural and attitudinal of the student as a contribution to the achievement of national identity. Likewise, the effectiveness of intercultural education, starting from the recognition and overcoming of the old colonial power structures, is based on the construction of a new educational-epistemological and social reality; that demands a new type of mentality for social actors, with the school being the main one in charge of carrying out this endeavor; This requires the improvement of the curriculum of Sciences that allows achieving its relevance and with it the integral development of the individual. Context in which ethical teacher training based on the principles of intercultural education, citizenship and democracy takes on a unique role as it is in charge of implementing the curriculum, methodologies and intercultural education.
Con el propósito de determinar cuáles factores contribuyen al empoderamiento de lo nuestro por parte de los niños(as) en el contexto de las Ciencias Sociales en la Enseñanza Básica se realizó un estudio de revisión bibliográfica, sistematizado a través de los métodos de análisis de contenido. Entre los principales hallazgos se determinó que entre estos factores la literatura señala las metodologías interactivas, la efectividad de la educación intercultural, la pertinencia curricular y la formación docente. En este empoderamiento las metodologías interactivas orientadas a enseñar y aprender desde una visión integradora e interdisciplinar, de participación activa, cooperación y colaboración en la construcción colectiva del conocimiento, transversalizadas por los saberes interculturales y los valores cívicos, patrióticos y éticos propician el desarrollo cognitivo, procedimental y actitudinal del estudiante como contribución al logro de la identidad nacional. Asimismo, la efectividad de la educación intercultural, partiendo del reconocimiento y superación de las viejas estructuras de poder colonial se basa en la construcción de una nueva realidad educativa-epistemológica y social; que reclama de un nuevo tipo de mentalidades los actores sociales, siendo la escuela la principal encargada de llevar a cabo este empeño; lo que requiere del perfeccionamiento del currículo de las Ciencias Sociales que permita lograr su pertinencia y con ello el desarrollo del individuo. Contexto en el que la formación ética del docente basado en los principios de la educación intercultural, la ciudadanía y la democracia cobra un singular rol al ser el encargado de implementar el currículo, las metodologías y la educación intercultural.
Keywords: FORMACION CIUDADANA; INTERCULTURAL; VALOR CIVICO